Development of Lighting System Simulator Student Worksheet to Improve CPS Skills of Vocational Students - Putrawijaya, Yori Septian; Handoyono, Nurcholish Arifin (Universitas Pendidikan Mandalika, 2024)
This research aims to develop and test the feasibility of the student worksheet lighting system to improve collaborative problem solving (CPS) skills of vocational students. This research method used research and development with the 4D model consists of stages, namely Define, Design, Develop, and Disseminate. The developmental research was conducted at class XI Vocational High School Muhammadiyah 1 Bambanglipuro, with teachers and students as the research subjects. Techniques in collecting data in this study used interviews, questionnaires, and documentation. This research instrument used consists of interview sheets, validation sheets for material experts and media experts, and student response questionnaires. Data analysis techniques use quantitative descriptive. The results of this research and development obtained student worksheet lighting system products that can improve CPS skills. The final results of the feasibility of the student worksheet information system show the following numbers: 90% by material experts, 83% by media experts so that they are included in the